Osmotic dehydration of carrot in sugar beet molasses: Mass transfer kinetics - Koprivica Gordana B. (Acta Periodica Technologica, 2010)
The osmotic dehydration process of carrot in sugar beet molasses solutions (40, 60 and 80%), at three temperatures (45, 55 and 65°C) and atmospheric pressure, was studied. The main aim was to investigate the effects of immersion time, working temperature and molasses concentration on mass transfer kinetics during osmotic dehydration. The most important kinetic parameters were determined after 20, 40, 60, 90, 120, 180, 240 and 300 min of dehydration. Diffusion of water and solute was the most intensive during the first hour of the process and the maximal effect was observed during the first 3 hours of immersion. During the next two hours of dehydration, the process stagnated, which implied that the dehydration time can be limited to 3 hours.